A novel small molecule RK-019 inhibits FGFR2-amplification gastric cancer cell proliferation and induces apoptosis in vitro and in vivo - Zeng, Jun; Ran, Kai; Li, Xinyue; Tao, Longyue; Wang, Qiwei; Ren, Jiangtao; Hu, Rong; Zhu, Yongxia; Liu, Zhihao; Yu, Luoting (Frontiers in Pharmacology, 2022)
Gastric cancer (GC) is one of the most malignant cancers, and is estimated the 5th incidence ratio and 3rd leading cause of cancer death worldwide. Despite advances in GC treatment, poor prognosis and low survival rate necessitate the development of novel treatment options. Fibroblast growth factor receptors (FGFRs) have been suggested to be potential targets for GC treatment. In this study, we report a novel selective FGFR inhibitor, RK-019, with a pyrido [1, 2-a] pyrimidinone skeleton. In vitro, RK-019 showed excellent FGFR1-4 inhibitory activities and strong anti-proliferative effects against FGFR2-amplification (FGFR2-amp) GC cells, including SNU-16 and KATO III cells. Treatment with RK-019 suppressed phosphorylation of FGFR and its downstream pathway proteins, such as FRS2, PLCγ, AKT, and Erk, resulting in cell cycle arrest and induction of apoptosis. Furthermore, daily oral administration of RK-019 could attenuate tumor xenograft growth with no adverse effects. Thus, RK-019 is a specific FGFR inhibitor with potent anti-FGFR2-amp GC activity both in vitro and in vivo.